Evolución de preferencias bajo escenarios de información completa e incompleta: Teoría y evidencia experimental - Salazar, César; Villena, Mauricio (Estudios de Economía, 2016)
This research has been divided into two main parts. First we use elements of Evolutionary Game Theory (EGT) to examine the evolutionary stability of different types of preferences in the context of common property resource exploitation. Particularly, we analyze the evolutionary stability of selfish, altruistic, and spiteful preferences using an “indirect evolutionary approach” as put forward by Bester and Güth (1998). The basic results of our theoretical model suggest that in a scenario of complete information, spiteful preferences will be evolutionarily stable implying an exploitation effort level above the Nash equilibrium. By contrast, in the context of incomplete information about individual preferences, selfish preferences are the ones that are evolutionarily stable. Second, we experimentally evaluate the theoretical results derived in the first part of the paper, considering both complete and incomplete information scenarios. In order to do this, we use two distinct treatments of the standard experiment of a CPR game, which are based on the work of Walter et al. (1990), who model the classic problem of CPR exploitation as an abstract investment decision. Comparing the distinct theoretical predictions with the experimental results using statistical significance criteria we found that the theoretical predictions based on EGT explain better the experimental results than the predictions based only on non-cooperative game theory.